WRITING RECOUNT TEXT THROUGH JOURNALISTIC QUESTIONS METHOD: Teaching Writing Recount Text, Journalistic Questions Method in Generating Ideas in Writing Recount Text, Students’ participation in using journalistic questions method in writing recount text, Stages of Learning Journalistic Questions Method in Writing Recount Text, C. Students’ Responses Toward Journalistic Questions Method in Writing Recount Text. - Melga Alvina Melga Alvina; Yousef Bani Ahmad (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2021)
The researcher chooses this title because she found students who have difficulties to start writing at tenth grade students in SMAN 1 Mandirancan. Therefore, the aimed of the research are to know the students’ responses toward Journalistic Questions Method and to know how Journalistic Questions can be applied in teaching writing recount text at tenth grade students of SMAN 1 Mandirancan. The research was conducted using the descriptive qualitative method. The participant of this research was the second semester of X social 3, academic year 2019/2020. The data were gathered from the writing practice using journalistic questions method in the recount text. There are two instruments used in this research, i.e. interview and documentation. In conclusion, using Journalistic questions method has positive responses for students and be able to facilitate the students in writing learning process.